Carbon-branched carbohydrate chirons: practical access to both enantiomers of 2-C-methyl-ribono-1,4-lactone and 2-C-methyl-arabinonolactone - Booth, K; da Cruz, F; Hotchkiss, D; Jenkinson, S; Jones, N; Weymouth-Wilson, A; Clarkson, R; Heinz, T; Fleet, G (2008)
Readily crystallized 2-C-methyl-d-ribono-1,4-lactone is formed in a one-pot procedure from d-glucose without any protecting groups by treatment with dimethylamine to give an Amadori ketose and then with aqueous calcium hydroxide in yields of approximately 25%; 2-C-methyl-l-ribono-1,4-lactone is similarly produced from l-glucose. 3,4-O-Isopropylidene-2-C-methyl-d-arabinono-1,5-lactone and 2-C-methyl-d-arabinono-1,4-lactone were prepared in a combined 60% yield by the Kiliani reaction of sodium cyanide with a protected 1-deoxy-d-ribulose derived from d-erythronolactone; the enantiomeric arabinonolactones are similarly available from l-erythronolactone. © 2008 Elsevier Ltd. All rights reserved.